Efficient catalytic effect of the page-like MnCo2O4.5 catalyst on the hydrogen storage performance of MgH2. Issue 21 (21st September 2022) - Zhou, Shiming; Wei, Dan; Wan, Haiyi; Yang, Xiu; Dai, Yujuan; Chen, Yu'an; Pan, Fusheng
Abstract : MnCo2 O4.5 is decomposed into a variety of catalytically active substances during the de/hydrogenation process, which greatly promotes the hydrogen storage performance of MgH2 . Abstract : Binary transition metal oxides have exhibited highly excellent de/hydrogenation kinetic catalytic properties on magnesium hydride (MgH2 ). Thence, page-like MnCo2 O4.5 nanoparticles have been synthesized to enhance the de/hydrogenation performance of MgH2 . The initial dehydrogenation temperature of the MgH2 -6 wt% MnCo2 O4.5 composite decreases to 285 °C. Interestingly, MgH2 doped with 6 wt% MnCo2 O4.5 can fully release 6.4 wt% H2 in 4 min at 325 °C. On the contrary, only 0.58 wt% of H2 is released from the undoped as-milled MgH2 in 4 min at 325 °C. Moreover, the dehydrogenated MnCo2 O4.5 doped composite can absorb 4.43 wt% H2 in 30 min at 150 °C. Moreover, we found that the desorption activation energy of the composite decreases by 50.18% compared with that of the undoped as-milled MgH2 . The evolution process and catalytic mechanism of MnCo2 O4.5 on MgH2 were explored through the evidence of X-ray diffraction and transmission electron microscopy. It is believed that Mn-containing phases and Co-containing phases formed in situ during the dehydrogenation process can synergistically catalyze MgH2 to achieve better kinetic performance.